A Comparative Study of Nomegestrol Acetate and a Combination of Ethinylestradiol and Levonorgestrel for Delaying Menstruation among Umrah Pilgrims - Tindar, Mirzah; Effendi, Yusuf; Abadi, Adenan; Theodorus, Theodorus (Indonesian Socety of Obstetrics and Gynecology, 2018)
Objective: To compare the effectiveness efficacy of nomegestrolacetate with and combination of ethinylestradiol and levonorgestrelas a regimen for delaying menstruation in Umrah pilgrims in Palembangcity.Methods: This single-blind randomized controlled trial was conductedin Hajj and Umrah Guidance Group in Palembang city duringDecember 2016 to January 2017. Population of this study was 30women who meet the inclusion and exclusion criteria. Frequencyand distribution of data was described in a table. Effectiveness andthe side effects treatment between the two groups were analyzedwith Chi Square test. Data was were analyzed using SPSS version18.0.Results: There were no differences in age, education, occupation,parity, body weight, height and contraceptive history betweentwo both groups (all p values > 0.05). Statistical analysis showedthere was no difference in spotting between nomegestrol acetate5 mg or a combination of levonorgestrel 150 mcg and 30 mcgethinylestradiol in Umrah pilgrims (p = 1.000). Other side effectssuch as (dizziness, depression, breast tenderness, heavy limbs,nauseam and vomiting) between the two groups could not beanalyzed because all subjects did not experience any other sideeffects.Conclusion: There is no difference in effectiveness betweennomegestrol acetate 5 mg or combination of levonorgestrel 150mcg and 30 mcg ethinylestradiol as a regimen for delayingmenses in Umrah pilgrims in Palembang city.[Indones J Obstet Gynecol 2018; 6-1: 45-49]Keywords: delay menstruation, ethinylestradiol, levonorgestrel,nomegestrol, side effects, spotting, umrah